Surau and Modernization of Early 20th Century Islamic Education Case of Western Sumatra (Minangkabau) - Zulman, Herry; Samad, Duski (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The study aims to investigate the Surau transformation and modernization in the development of Islamic education in the early 20th century in Western Sumatra. The method used is a library study. In general, Surau, as a center of Islamic learning, has an important role in the development of Islam and the understanding of its teachings. Surau has been the birthplace of many of Minangkabau's great scholars and has played a role in nurturing the spirit of nationalism against the Dutch colonization. Besides, Surau is also one of the oldest Islamic educational institutions in Western Sumatra.In addition to serving as a place of worship such as prayer and teaching, Surau is also a place to study various religious sciences such as fiqih, mantiq, and tafsir. Fiqih became the main focus of the defense at Surau. Surau's transformation into a madrasah was marked by a shift in learning patterns from the tradition of sitting on a chair to using chairs, tables, and desks. The modernization of Surau into a madrasah has expanded steadily in several locations in Western Sumatra such as Padang, Highlands, Sungayang, Baso, and other locations. Characters such as Syeih HM Thaib Umar, Abdul Ahmad, Abdul Karim Amarullah, Jamil Jambek, Sulaiman Arrasul, and others are recognized as the main drivers of Islamic modernization in Minangkabau.